Recent Research on Indexation and the Housing Market - Cohn, Richard A.; Lessard, Donald R. (Journal of Finance, 1976)
Richard A. Cohn, Donald R. Lessard, Recent Research on Indexation and the Housing Market, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 403-413